PELATIHAN ETIKA PROFESIONAL SDM SEBAGAI FAKTOR PENENTU KEBERLANJUTAN ORGANISASI PKBM MERAH PUTIH DI KABUPATEN MALANG - Deni Nugroho Setyabudi; Ririn Ningkeula; Arinta Agnie Dewantari; Firmansyah Mochsen (JPM PAMBUDI, 2023)
All organizations have an obligation to develop human resources in such a way that their desires are guaranteed. An organization is expected to be able to easily prepare and implement each program or work plan if it has quality human resources with an understanding and comprehension of professional ethics. All people who are directly involved in managing an organization must have an awareness of professional ethics so that their relationships can function well. Furthermore, organizational operations occur according to the vision, mission, goals and approaches that have been determined. Professional ethics training helps create an organizational environment and ecosystem that leads to effective and efficient organizational development. All of our employees are united by professionalism, courtesy, character and integrity. Human resources who have a good work ethic also make it easier to carry out activities such as developing human resource management, leadership development and entrepreneurship. By carrying out training and understanding professional ethics, it is hoped that the organization's desires based on good corporate governance can be achieved.